Resveratrol inhibits bladder cancer proliferation by targeting the AURKA/STAT3 axis: From computational analysis to experimental validation - Chao Feng; Guodong Chen; Yan Shu; Jing Chen; Wenxin Ye; Ligang Ren (PLoS ONE, 2026)
Introduction Given the high recurrence rate of bladder cancer (BCa) and the significant adverse effects associated with conventional treatments, it is urgent to search for new clinical therapeutic targets and safer natural-derived compounds. Resveratrol (Res) has been demonstrated to exhibit cytotoxicity against various tumors. However, the signaling pathways and targets involved in inhibition of BCa cells still need further exploration. This study aims to investigate the mechanism of Res in Bca via suppression of the AURKA/STAT3 axis, providing important theoretical basis for subsequent further researches on Res for treating BCa. Methods Differentially expressed genes were identified through bioinformatics methods and the binding sites of resveratrol were also identified. The cell survival rate was detected by the CCK8 method to calculate the concentrations of Res for 30% inhibition and for 50% inhibition. Then, flow cytometry was used to detect the cell cycle and apoptosis after treatment with different concentrations of Res. Immunofluorescence staining was used to detect the effects of Res and MLN8237 on the expression of STAT3. Western blot and qPCR analyses were used to verify the reliability of the effects of Res and MLN8237 on target proteins. Results AURKA was identified as the potential target of Res by computational analysis. Further validation through CCK8 assays and flow cytometry demonstrated that Res could inhibit BCa cells and their cell cycle in a time- and dose-dependent manner. Immunofluorescence staining revealed both Res and MLN8237 suppressed STAT3 expression in BCa cells. Additionally, western blot and qPCR analysis confirmed that Res and MLN8237 inhibited the expression of AURKA and known target genes (VEGF, Bcl-2, and Cyclin D1). Conclusion Our findings suggest that Res may regulate BCa cell expression through the AURKA/STAT3 axis, providing a theoretical foundation for the structural optimization of Res and the development of multi-target drugs for clinical application.